Effectiveness of Human Capital on Employee Performance in the Era of Disruption in the Health Sector - Wulandari, Retno; Nurannisa, Fitri Revita (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The era of disruption has affected the mentality and human resources way of working in public health. In this era, human resources in the health sector play a crucial role in public health digitalization. It aims to determine the effectiveness of human capital on employee performance in the era of disruption in the health sector. The research method applied in this study is quantitative with a cross-sectional approach. This research was conducted at the Tawangrejo Health Center from January to March 2022. The population of this study is the entire employee, with the amount of 70 people. To determine the sample, the researcher used Slovin Formula with an accuracy of 0,1. As result, 42 respondents were obtained. Data collection was carried out using a questionnaire distributed to all respondents. Furthermore, data analysis in this research is applying ordinal regression tests. The result of the study shows that there is no effect of human capital on employee performance, where the value of sig ≥ 0,720 provides the meaning of no influence for two variables. Moreover, the discovered value of Nagelkerke in this research is 0,025 showing between the two variables have no effect by 2,5%. Based on that finding, the public health should about its employees’ performance by optimizing the existing human capital, so this will not affect the organization’s sustainability in the future.